Coordination of Multi-Robot Systems - GUETTAF, Wahid (Mohamed Boudiaf University of M’sila, 2026)
Thisthesisfocusesonthecoordinationofmulti-robotsystems,particularlyonfor mationcontrol andthe integrationof safetymechanisms indynamic environments. AmethodologycombiningControlBarrierFunctions(CBFs)andHigher-OrderCon trolBarrierFunctions (HOCBFs) isdevelopedtoensurecollisionavoidanceandal lowcontrolledformationdeformation. Casestudiesdemonstratetheeffectivenessof theproposedframeworkinmaintainingsafetyandcoordinationincomplexscenarios. Thisworkopensupprospects forapplications inareassuchasautonomous robotics andsurveillance.Futureresearchwillexploretheintegrationofmachinelearningand improvingresilienceagainstattacks.
Keywords: Multi-robotsystems; Formationcontrol; CBFandHOCBF; Safety; Con- trolleddeformation; Decentralizedcoordination